EXPERIENCES OF NON-CONSENSUAL SEX AMONG STUDENTS OF THE POLYTECHNIC IBADAN, NIGERIA (2012)
Non-Consensual Sex (NCS) encompasses a range of behaviours including unwanted sexually motivated touch, attempted rape, rape and non-contact forms of sexual abuse such as forced viewing of pornography. It is a major cause of reproductive health problems such as unwanted pregnancy, unsafe abortion and sexually transmitted infections. In Nigeria, previous studies on NCS largely focused on adolescents in secondary schools. More studies on the experiences among students in tertiary institutions need to be carried out to highlight the burden in these young adults. This study was aimed at determining the experiences of NCS among students of The Polytechnic Ibadan. A cross-sectional survey was conducted among 594 students who were selected from the four halls of residence in The Polytechnic Ibadan using a four-stage random sampling technique. Quantitative data were collected using a self-administered questionnaire which explored respondents’ demographic characteristics, sexual behaviour, experiences of NCS during the six months preceding the study and help-seeking behaviour. Qualitative data were collected using In-Depth Interview (IDI) of fourteen consenting victims of NCS. Descriptive statistics, Chi-square and logistic regression were used to analyse the quantitative data with level of significance set at 0.05 while the qualitative data were analysed using thematic approach. Mean age of respondents was 22.7 ± 2.9 years and 58.9% were females. Fifty-six percent of respondents had experienced sexual intercourse and the mean age of sexual debut was 19.6 ± 3.2 years. Thirty three percent of the respondents had experienced at least a form of NCS and out of these, 61.7% were females. Forms of NCS experienced by respondents included unwanted touch of breast or back side (18.0%), forced viewing of pornography (4.5%), attempted rape (7.4%) and rape (4.0%). Rape victims consisted of 54.2% females and 45.8% males. Out of those who were sexually experienced, 9.0% reported that their first sexual intercourse was due to rape. Respondents with a history of alcohol use (OR = 1.5, 95% CI = 1.03-2.23) and those who had a friend of the opposite sex (OR = 7.5, 95% CI = 1.75-31.8) were more likely to report the experience of any form of NCS. Significantly, males who had ever drunk alcohol reported the experience of unwanted touch than those who had never (21.5% vs 9.5%). Well known friends of the victims were the major perpetrators of all forms of NCS; unwanted touch (93.0%), forced viewing of pornography (95.4%), attempted rape (92.8%) and rape (76.5%). Female rape victims reported that lecturers were the perpetrators (23.0%) and they did not seek help (82.4%). This was corroborated by the IDI results which showed that the only person who sought help among females visited a patent medicine seller. In-depth interview also revealed that most of the victims were raped at the perpetrator’s residence and the perpetrators were their acquaintances. Non-consensual sex remains a social problem among the target population. However, attempt to seek help was a rare practice. This underscores the need to develop health education programmes that will enable polytechnic students to prevent the phenomenon and seek help when experienced.